The frequency of CLA(+) CD8(+) T cells in the blood of psoriasis patients correlates closely with the severity of their disease - Sigmundsdóttir, H (Blackwell Science Inc, 2001)
Psoriasis is thought to be a T cell-mediated skin disease and the cutaneous lymphocyte antigen (CLA) is an important skin homing epitope for T cells. We have studied the relationship between disease severity (PASI) and phenotypic analysis of T cells in the blood of 36 patients with psoriasis focusing on the expression of CLA, VLA-4 and CD25 on CD4(+) and CD8(+) T cells. The patients had a higher frequency of circulating CLA(+) CD8(+) cells than healthy controls. Furthermore, a much stronger correlation was observed between PASI and the frequency of CLA(+) CD8(+) than CLA(+) CD4(+) T cells. The frequency of CLA(+)D8(+) T cells correlated more strongly with redness, thickness and scaling of the skin lesions than the total affected body surface area. In contrast to CLA the T cell expression of VLA-4 did not demonstrate any such correlation. Finally, the expression of the activation marker CD25 on CD8(+) T cells showed a strong correlation with disease severity in patients with moderate to severe psoriasis (PASI > 10) but such correlation was not observed for CD4(+) T cells. These findings support the notion that circulating CLA(+) CD8(+) T cells may play an important role in the pathogenesis of psoriasis.